A (des) necessidade da oitiva do adotado, quando de seu desconhecimento de vida familiar biológica: um olhar crítico e afetivo! - Tramontini, Victória (2023)
This work presents an analysis of the articles set out in the Statute of Children and Adolescents, with emphasis on article 28, §2 of the Child and Adolescent Statute and the existing factual situation of the the protected person’s lack of knowledge regarding their history. To this end, he discussed the history of women's rights children and adolescents, as well as forms of adoption. Furthermore, recent decisions on the need for specifics to the subject and decisions indicating the need for a hearing from the protected person due to of ignorance, in compliance with other evidence contained in the process. It was noticed that the look judicious and affective aims to protect the principle of human dignity and ensure the right to origins, principles essential to the best interests of the infant.